Determinación de las condiciones de uso del almidón modificado en el mejoramiento de formulas alimenticias - Fabián, Vera A. (2011)
The use of thickeners in the food industry is increasing constantly, because of the challenge to provide cheaper alternatives to the consumer of finished products, as well as comply with local regulations. However, in Ecuador, the supply of thickening is not very diverse, because the marketing is managed by houses which don’t have the necessary resources or trained personnel to improve and adapt their applications to local needs. Typically, thickeners used are: carboxymethyl cellulose (CMC), xanthan gum and guar gum, whose applications in cost-dose expensive the final product. On this basis, I propose as an alternative low-cost use of modified starches. One of the limitations in the use of modified starches is that the applications suggested by the manufacturer, this is, pH, temperature and addition of water, often do not provide the desired results in the final product because the process conditions and as, the raw materials used differ from those that are marketed locally. That is as, this report seeks to determine the suitable conditions of its implementation through the development of new formulations and / or partial or total replacement of existing formulas. For this purpose, experimental tests were done in semi-preserves: Tomato Sauce ketchup, canned fish such as sardines in tomato sauce and Albacora in cassava –onions sauce, as well as bakery products such as bread mold type. The results can be evidenced in the development of modified starch sheet and manufactured products are marketed in the local market.e.